Breathomics from exhaled volatile organic compounds in pediatric asthma. Issue 12 (30th October 2017) - Neerincx, Anne H.; Vijverberg, Susanne J. H.; Bos, Lieuwe D. J.; Brinkman, Paul; van der Schee, Marc P.; de Vries, Rianne; Sterk, Peter J.; Maitland‐van der Zee, Anke‐Hilse
Abstract: Asthma is the most common chronic disease in children, and is characterized by airway inflammation, bronchial hyperresponsiveness, and airflow obstruction. Asthma diagnosis, phenotyping, and monitoring are still challenging with currently available methods, such as spirometry, FE NO or sputum analysis. The analysis of volatile organic compounds (VOCs) in exhaled breath could be an interesting non‐invasive approach, but has not yet reached clinical practice. This review describes the current status of breath analysis in the diagnosis and monitoring of pediatric asthma. Furthermore, features of an ideal breath test, different breath analysis techniques, and important methodological issues are discussed. Although only a (small) number of studies have been performed in pediatric asthma, of which the majority is focusing on asthma diagnosis, these studies show moderate to good prediction accuracy (80‐100%, with models including 6‐28 VOCs), thereby qualifying breathomics for future application. However, standardization of procedures, longitudinal studies, as well as external validation are needed in order to further develop breathomics into clinical tools. Such a non‐invasive tool may be the next step toward stratified and personalized medicine in pediatric respiratory disease.